(untitled) (Alternautas, 2022)
Ever more acute socio-ecological problems demand a reorientation of natural resource-intensive growth paths. In this regard, the Ecuadorean “healthy and good life index” (Indice de vida saludable y bien vivida, IVSBV) offers alternatives for measuring quality of life.Discussing sedimented ideas of wellbeing and the meaningfulness of its measurements, as well as the introduction of the variable “time” as a determinant of social development, seeks to advance a socioecological model.